1933
DOI: 10.1017/s0022172400018672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition toBacillus piliformisInfection among Mice

Abstract: Tyzzer (1917), who described an epidemic that had appeared in his mouse colony, named the causative organism Bacillus piliformis, giving an inclusive description of its behaviour and morphology. Both natural and experimental infections were studied. The high susceptibility of the Japanese waltzers as contrasted with the relative immunity of the common mice suggests that the disease susceptibility may be linked with the waltzing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1936
1936
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This statement by Gard concerning the sporeforming bacterium (Bacillus piliformis) which multiplies only within certain cells seems as appropriate today as 26 yr ago. Numerous reports (4,9,15,19) have confirmed Tyzzer's original description (20) of a fatal enteric disease of mice, since known as Tyzzer's disease. The diagnostic feature of Tyzzer's disease is the demonstration of bundles of gram-negative, pleomorphic bacilli (B. piliformis) randomly arranged in the cytoplasm of apparently viable liver cells which border small areas of coagulation necrosis.…”
mentioning
confidence: 77%
“…This statement by Gard concerning the sporeforming bacterium (Bacillus piliformis) which multiplies only within certain cells seems as appropriate today as 26 yr ago. Numerous reports (4,9,15,19) have confirmed Tyzzer's original description (20) of a fatal enteric disease of mice, since known as Tyzzer's disease. The diagnostic feature of Tyzzer's disease is the demonstration of bundles of gram-negative, pleomorphic bacilli (B. piliformis) randomly arranged in the cytoplasm of apparently viable liver cells which border small areas of coagulation necrosis.…”
mentioning
confidence: 77%
“…The demonstration that some strains of animals are resistant and others susceptible to infection by a given strain of micro-organism has been known for many years (Lewis and Loomis, 1928;Gowen and Schott, 1933) and several mechanisms have been proposed to explain this phenomenon (Eastwood, 1927). Particular strains of mice that differ in susceptibility to infection by S. typhimurium have been known for some time (Gorer and Schutze, 1938) and it has been suggested that genetically determined resistance might operate through the presence of opsonising antibodies which enhance clearance of S. typhimurium from the circulation of infected animals (Rowley and Jenkin, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…The meiotic peculiarities described for claret of D. simulans are seemingly under genic control. In D. melanogaster the important instances of apparent genic control of nondisjunction and chromosome loss are those reported for claret-nondisjunctional (LEWIS and GENCARELLA 1952) and for C3G (GOWEN 1933).…”
mentioning
confidence: 86%